Ethno-Religious Identification and Social Distance Between Muslims and Christians: Analysis on Social Identity Theory - Cahyo Pamungkas (Journal of Indonesian Social Sciences and Humanities, 2018)
This article aims to investigate the relationship between ethno-religious identity and the social distance between Muslims and Christians in Ambon and Yogyakarta, taking into account factors at the individual level. Also, this research is addressed to fll a gap in the literature between studies that emphasize economic and political competition as the main sources of con?ict, and studies that focus on prejudice and discrimination as causes of con?ict. The central question is: to what extent is ethno-religious identifcation present among Muslims and Christians in Ambon and Yogyakarta and observable in their daily lives? This research uses social identity theory that attempts to question why people like their in-group, and dislike out-groups. The theory says that individuals struggle for positive in-group distinctiveness, and have positive attitudes toward their in-group and negative attitudes towards out-groups. This research uses both quantitative and qualitative approaches. A survey was conducted with 1500 university students from six universities in Ambon and Yogyakarta. By using quantitative and qualitative methods of analysis, this study came up with several fndings. Firstly, the study found high levels of religious identifcation among Muslim and Christian respondents, demonstrated by their participation in religious practices, which we defne as frequency of praying, attending religious services, and reading the Holy Scriptures. Secondly, social distance consists of contact avoidance, avoidance of future spouses from another religion, and the support for residential segregation. Differences from the mean show that Muslim respondents tend to display higher contact avoidance and support for residential segregation compared to Christian respondents. Thirdly, analysis of variance demonstrates that elements of ethno-religious identity are related signifcantly to elements of social distance.